High-octane Leadership: building a resilient and futuristic organisation- A Critical Perspective - Ganguly, Prof. Dr Abhijit (International Journal of Scientific Research and Management (IJSRM), 2017)
Professor- University of Northwest Europe, NetherlandSenior Lecturer (Sessional)-Global Banking School, LondonSenior Lecturer(Sessional)-London School of Business and Management, LondonSenior Faculty-Eaton Business School ( Westford Group),UKAdjunct Professor-EMPI Business School, New DelhiManagement Consultant- Qualtrain Consulting Inc., London, New York, Toronto, Sydney, Dubai